Latitudes + Parallels : Focus on Contemporary Canadian Photography. (Winnipeg : Winnipeg Art Gallery, 1983)
Arnold, Grant ; Applebaum, Isaac ; Ballantyne, David ; Bradley, Randy ; Campeau, Michel ; Cattroll, Fred ; Charter, Ed ; Cohen, Lynne ; Condron, Brian ; Evans, Steven ; Flomen, Michael ; Gasoi, Marvin ; etc.
Latitudes + Parallels : Focus on Contemporary Canadian Photography / Latitudes + Parallèles : Convergences sur la photographie Canadienne contemporaine, The Winnipeg Art Gallery, Winnipeg, May 26 - July 10, 1983
Engels & Frans
kunstcatalogus
Keywords: Canada